Understanding company law - Hudson, Alastair (Routledge, 2025)
"Understanding Company Law is a lively introduction to modern company law. It takes a unique approach to the subject, which also encompasses the important and growing fields of securities regulation, corporate governance and corporate social responsibility. This textbook covers all of the key topics that a student reader will encounter in any company law course. The discussion presents the key principles simply, before guiding the reader through the more complex issues that are often the focus of examinations in this subject. It also offers pathways into further reading, while injecting enjoyment back into the topic. Understanding Company Law provides a straightforward guide to the law, which is supported by context, detailed analyses of the leading cases, and humour. The third edition has been updated with key recent changes and developments in company law, both case law and statutory, including: the Economic Crime and Corporate Transparency Act 2023, the UK Corporate Governance Code 2024, the Financial Services and Markets Act 2023 and discussion of recent corporate scandals and case law. It will be essential reading for all courses on company law"--